2020
DOI: 10.1590/1809-6891v21e-60058
|View full text |Cite
|
Sign up to set email alerts
|

Morphometry of infraorbital foramen applied to local anesthesia in hoary fox (Lycalopex vetulus Lund, 1842)

Abstract: Whilst considering the need anesthetic techniques supported by species-specific morphology, it has been sought to describe the morphometry of the Hoary Fox's infraorbital foramen with aims at correlating its topography with points of anatomic reference in the skull, thereby providing subsidy for a more effective local anesthetic block in that species. Four skulls of Lycalopex vetulus had been used, from which all of the measurements in each antimere were performed. The infraorbital foramen was located at the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…19 It is necessary for the surgeon to be familiar with, and to preserve as much as possible all vascular and neural structures involved, with concern not only for surgical risk, but also for preservation of the tissue and the structures responsible, in order to maintain their vitality and normal function. [20][21][22][23] In agreement with a previous study, 14 this study showed that dogs have an advantage in that their arteries can form multiple anastomoses, re-establishing the blood supply in damaged areas.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…19 It is necessary for the surgeon to be familiar with, and to preserve as much as possible all vascular and neural structures involved, with concern not only for surgical risk, but also for preservation of the tissue and the structures responsible, in order to maintain their vitality and normal function. [20][21][22][23] In agreement with a previous study, 14 this study showed that dogs have an advantage in that their arteries can form multiple anastomoses, re-establishing the blood supply in damaged areas.…”
Section: Discussionsupporting
confidence: 92%
“…14,29 Alterations of the peripheral innervation of the head can also be due to neural dysfunctions and tumors originating from the neuronal fibers themselves, 30,31 and this knowledge is essential for local anesthesia in the head. [20][21][22][32][33][34][35] Healing of the oral mucosa is faster than that of the skin due to several factors, including a more abundant blood supply. 36 The temporary bilateral occlusion of the external carotid artery before major surgical procedures, such as maxillectomy and total mandibulectomy, in order to minimize blood loss due to accidental rupture of large vessels located in the infraorbital region or close to the temporomandibular joint is commonly performed in veterinary surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The common sloth has a skull with a small and compact shape, with a reduced opening of the oral cavity, foramina with a reduced circumference and a different positioning when compared to domestic animals, which alters access to the IF and MF using the techniques recommended for domestic animals such as dog and cat (Konig & Liebich, 2016;Snyder et al, 2018); and techniques described for wild animals such as rabbits, canids and primates (Engel et al, 2019;Magalhães et al, 2019Magalhães et al, , 2020Peña et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In this scenario, anatomical descriptions and morphometrics have become necessary and important sources for establishing more targeted protocols for such species. In the hoary fox (Lycalopex vetulus), a carnivorous canid, because of its anatomy and morphometry, both the IF and MF techniques were adapted in line with the particularities of the species (Magalhães et al, 2019(Magalhães et al, , 2020. For rhesus monkeys (Macaca mulata), the IF technique used is like the intraoral technique used in domestic animals, and for MF, the extraoral technique takes the mandible angle as a reference point instead of the angular process (Engel et al, 2019).…”
Section: Discussionmentioning
confidence: 99%